Integrated Technology of Data Remote Sensing and GIS Techniques Assess the Land Use and Land Cover Changes of Madurai City Between the Year 2003-2013 - Srinivasan, R.; Sathik, M. Mohamed (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
The present study focuses on the nature and pattern of urban expansion of Madurai city over its surrounding region during the period from 2003 to 2013. Based on its proximity to the Madurai city, Preparation of various thematic data such Land use and Land cover using Land sat data. Create a land use land cover map from satellite imagery using supervised classification. Find out the areas from the classified data. The study is based on secondary data, the satellite imagery has downloaded from GLCF (Global Land Cover Facility) web site, for the study area (path101 row 67), the downloaded imagery subset using Imagery software to clip the study area. The clipped satellite imagery has used to prepare the land use and land cover map using supervised classification.